Should procalcitonin be measured routinely in acute decompensated heart failure?. (July 2015) - Loncar, Goran; Tscholl, Verena; Tahirovic, Elvis; Sekularac, Nikola; Marx, Almuth; Obradovic, Danilo; Veskovic, Jovan; Lainscak, Mitja; von Haehling, Stephan; Edelmann, Frank; Arandjelovic, Aleksandra; Apostolovic, Svetlana; et al.
Aim: To elucidate the prognostic role of procalcitonin (PCT) in patients with acute decompensated heart failure (ADHF) without clinical signs of infection at admission.Materials & Methods: Serial measurements of PCT and NT-proBNP were performed in 168 patients, aged 68 ± 10 years with ADHF followed by 3-month outcome evaluation.Results: Cox regression analysis demonstrated significant predictive value of baseline PCT for all-cause death/hospitalization (area under the curve: 0.67; p = 0.013) at 90th day. The patients with persistently elevated PCT or with an increase during the first 72 h of hospitalization had the worst prognosis (p = 0.0002).Conclusion: Baseline and serial in-hospital measurements of PCT have significant prognostic properties for 3-month all-cause mortality/hospitalization in patients with ADHF without clinical signs of infection at admission.